2017
DOI: 10.1039/c7ra07465d
|View full text |Cite
|
Sign up to set email alerts
|

Facile one-pot synthesis of 3D graphite–SiO2 composite foam for negative resistance devices

Abstract: Facile one-pot synthesis of graphite–SiO2 foam for negative resistance devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
(70 reference statements)
0
9
0
Order By: Relevance
“…This peak can appear when a carbon atom is with other elements, due to some bonding with neighboring atoms (for example, CO, CH, etc. ), indicating that the PGR is low crystallinity graphite. The large peak at 288 eV of the standard graphite would be due to the natural oxidation, which is related to the freshness of the sample after opening the package. The 288 eV peak of a fresh sample should be much smaller.…”
Section: Resultsmentioning
confidence: 99%
“…This peak can appear when a carbon atom is with other elements, due to some bonding with neighboring atoms (for example, CO, CH, etc. ), indicating that the PGR is low crystallinity graphite. The large peak at 288 eV of the standard graphite would be due to the natural oxidation, which is related to the freshness of the sample after opening the package. The 288 eV peak of a fresh sample should be much smaller.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, soft XAS can probe bulk structure information such as crystalline or amorphous states and site occupation. For instance, Wu et al distinguished amorphous and crystalline SiO 2 through analysis of the peak features of the Si K-edge XAS by analyzing the peak features [ 87 ], and Zhang et al demonstrated that the Fe L-edge XAS can be an indicator of tetrahedral and octahedral coordination [ 74 ].…”
Section: Other Xas Applicationsmentioning
confidence: 99%
“…Figure 6b is the Si K-edge XAS around 1848 eV 29 . It shows that all Al-doped Si glasses are in the same amorphous phase as SiO 2 , which eliminates the phase transition influence 30 . In contrast, Al and O XAS spectra in Fig.…”
Section: Resultsmentioning
confidence: 90%